The Face Expressions Analysis of Woody in the Film Toy Story 4 - Jamada, Jamadi; Taufik, Muhammad (English Literature Studi Program Universitas Islam Makassar, 2024)
Toy Story 4 is a 2019 American 3D computer-animated. In this research, The problem of this research was to identify the various face expressions of Woody and find out what is the meaning behind the face expressions of Woody in the film Toy Story 4 because most of the audience only understood the meaning of the movie characters verbally, they rarely understood the meaning behind the non-verbal expressions. Therefore, the researcher took the initiative to find out the meaning behind woody’s face expressions in the film Toy Story 4 . the researcher formulates two research questions as follows: What kinds of face expressions are expressed by Woody in the film Toy Story 4 and What is the meaning behind Woody’s face expressions in the film Toy Story 4? The objectives of this research are :To find out the kinds of face expressions are expressed by Woody in the film Toy Story 4 and To find out the meanings behind Woody’s face expressions in the film Toy Story 4. In this research used descriptive qualitative. Based on the results of the research, the researcher managed to identify 48 total face expression data from 6 basic expressions by Ekman (1975) namely surprised, scared, happy, angry, sad, and disgusted in the film Toy Story 4 which focuses on the main character, Woody. This research also makes a significant contribution to the field of semiotics by examining how visual signs (face expressions) are used to convey meaning in a film work. This research is a good first step in understanding the complexity of face expressions in animated films Keywords: Face Expressions, Woody, Film, Toy Story 4, semiotic.